2023
DOI: 10.1007/s12325-023-02511-3
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Patient Perspectives on Artificial Intelligence; What have We Learned and How Should We Move Forward?

Abstract: Artificial intelligence (AI) in healthcare has now begun to make its contributions to real-world patient care with varying degrees of both public and clinical acceptability around it. The heavy investment from governments, industry and academia needed to reach this point has helped to surface different perspectives on AI. As clinical AI applications become a reality, however, there is an increasing need to harness and integrate patient perspectives, which address the distinct needs of different populations, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Additional reporting considerations are therefore needed that are not currently covered in TRIPOD 2015. Alongside methodological advancements, considerations of fairness, 62 wider acceptance of open science practices, 63 and public and patient involvement in research and implementation of research, 64 65 an update to the TRIPOD 2015 statement is needed to capture these developments and the consequences for reporting.…”
mentioning
confidence: 99%
“…Additional reporting considerations are therefore needed that are not currently covered in TRIPOD 2015. Alongside methodological advancements, considerations of fairness, 62 wider acceptance of open science practices, 63 and public and patient involvement in research and implementation of research, 64 65 an update to the TRIPOD 2015 statement is needed to capture these developments and the consequences for reporting.…”
mentioning
confidence: 99%
“…This perspective article is intended to contribute to our understanding of PFLE engagement in digital health and AI and this dynamic field of practice. While there is increasing recognition that PFLE engagement is crucial to the acceptability of AI in healthcare, engagement is predominantly overlooked in the development of AI or has a limited presence in academic literature (31)(32)(33). A recent scoping review on patient and public involvement in AI and digital health in mental health (33) found that only 5 of the 144 articles identified focused on PFLE, whereas most studies used and accessed patient and public perspectives to inform a project or co-design technologies.…”
Section: Discussion-critical Success Factors and Lessons Learnedmentioning
confidence: 99%
“…Successful implementation and adoption of AI in health care will require consideration of human factors beyond AI's predictive power and technological capabilities [29]. Patients and the public can serve as collaborators with AI in health care, either through public involvement, coproduction, co-design, or any similar methodology, and can thus shape a form of AI that addresses these concerns, a position shared by other projects [13][14][15][16][33][34][35]. In facilitating relevant PPIE activities, researchers need to be especially careful of the themes identified by this consultation: experience, empowerment, raising awareness, and acknowledging and supporting diversity in PPIE.…”
Section: Comparison With Previous Workmentioning
confidence: 99%